Serum sodium disorders in patients with traumatic brain injury - Paiva WS; Bezerra DA; Amorim RL; Figueiredo EG; Tavares WM; De Andrade AF; Teixeira MJ (Dove Medical Press, 2011)
Wellingson Silva Paiva, Douglas Alexandre França Bezerra, Robson Luis Oliveira Amorim, Eberval Gadelha Figueiredo, Wagner Malago Tavares, Almir Ferreira De Andrade, Manoel Jacobsen TeixeiraIntensive Care Unit, Division of Neurosurgery, Hospital Das Clinicas, University of São Paulo School of Medicine, São Paulo, BrazilAbstract: Sodium disorders are the most common and most poorly understood electrolyte disorders in neurological patients. The aim of this study was to determine the incidence of sodium disorders and its association with different traumatic brain injuries. This prospective study was conducted in 80 patients diagnosed with moderate and severe traumatic brain injuries. All patients underwent cerebral computed tomography. Incidence of sodium disorders, presence of injuries in the first computed tomography after traumatic brain injury, and level of consciousness were analyzed. Patients that presented other potential causes of sodium disorders and systemic trauma were excluded from the study. The incidence of sodium disturbances was 45%: 20 patients presented hypernatremia and 16 hyponatremia. Refers to all patients with sodium disturbances 53% were detected in the first sample. We recorded at least one measurement <125 mEq/L in 50% of the patients with hyponatremia. A greater incidence of sodium disorders was found in patients with subdural, intracerebral hematoma and with diffuse axonal injury. The incidence of sodium disorders among the patients with diffuse lesions was greater than in the group of patients with brain contusion (P = 0.022). The incidence of sodium disorders is higher in patients with diffuse traumatic brain injuries. No association was found between focal lesions and proportion of sodium disorders.Keywords: brain trauma, hypernatremia, hyponatremia